A Stability result for an inverse problem with integrodifferential operator on a finite interval - Mosazadeh, Seyfollah; Koyunbakan, Hikmet (Rocky Mountain Mathematics Consortium, 2020)
A boundary value problem consisting of an integrodifferential equation, together with boundary conditions dependent on the spectral parameter, is investigated. The asymptotic behavior of the eigenvalues is studied, and we prove the uniqueness and the stability theorems for the solution of the inverse problem. © Rocky Mountain Mathematics Consortium.
Keywords: Integrodifferential equation; Inverse problem; Stability theorem; Uniqueness theorem; Volterra integral operator